PENGARUH MODEL PEMBELAJARAN BERBASIS MASALAH TERHADAP HASIL BELAJAR KOGNITIF SISWA KELAS VII SMP - Insar Damopolii; Aksamina M. Yohanita; Febilia H. Malatta; Frida M. Yusuf (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2018)
The purpose of research to determine that effect of problem-based learning (PBL) model on cognitive student achievement in SMP YPPGI Silo Manokwari in the relation of population density to the environmenttopic. The study was a quasi-experimental research used nonequivalent control group design. The sample of the study was the students of class VIIA such as experimental class and the total students as many as 23students and the class VIIB such as the control class and the total students as many as 22 students. That result showed the experimental class to implementation PBL model obtained the average posttest 70,78, while the class control obtained the average posttest 50,05. The significant value was 0,01 < α = 0,05, there were different cognitive student achievement between the experiment class and the control class. Conclusion, there are differences in cognitive students achievement between students taught using PBL model with students taught using a conventional learning model.